(untitled) (Applied Biological Research, 2018)
Natural products in insect pest management programs have gained recognition due to environmental pollution, pest resistance and resurgence caused by indiscriminate use of synthetic pesticides. An attempt was made to find out ecofriendly pest management strategies by utilizing locally available botanical and vermiwash extracts during rabi, 2015-16 at College of Agriculture Vijayapur (India), to assess compatibility between vermiwash and botanicals ant their effect on pod borer, Helicoverpa armigera (Hubner), in chickpea ecosystem. The botanical extracts, viz. Parthenium hysterophorus and Vitex nigunda, neem seed kernel extract (NSKE) and garlic-chilli kerosine extract (GCKE) were evaluated alone or in combination with vermiwash (10%.). The results revealed that the plots treated with vermiwash @ 10% + NSKE @ 5% or vermiwash @ 10% + GCKE @ 3% recorded less number of eggs and larva of H. armigera. Further, in these treatments less pod damage and high grain yields were observed. Vermiwash treatment alone recorded highest number of eggs, larvae and pod damage as compared to other treatment-combination but was superior in number of natural enemy, Campoletis chloridae. Further, grain yield in this treatment was inferior to botanical treatments but significantly superior over untreated control, followed by Vitex nigunda (5%).